Removal of Bisphenol A Using Laccase‐Catalyzed Electrooxidation in the Presence of Humic Acid. Issue 9 (29th July 2022) - Nguyen, Khanh Hoang; Dao, Van‐Duong; Ngo, Thi Thuy Huong; Nguyen, Thi Hanh Tien; Nguyen, Quoc Tuan; Le, Thanh Thao
Abstract: Bisphenol A (BPA) is an endocrine‐disrupting chemical that has caught a lot of attention recently due to its toxicity and ubiquitous presence in the environment. Therefore, removal of BPA from contaminated environments such as water is of high importance. In this study, an alginate/pectin anode containing immobilized laccase is prepared, and the anode is applied in an electroenzymatic oxidation system for BPA degradation. After 4 h, the laccase–alginate/pectin system demonstrates a much higher BPA removal efficiency (95%) than the similar system without immobilized laccase (50%, control system). The effects of humic acids (HA) on BPA degradation are also observed. HA may have accelerated the laccase‐catalyzed coupling reaction between BPA and reactive radical intermediates, which results in increased BPA removal efficiency (92% after 150 min). It is demonstrated that laccase immobilization on an alginate/pectin electrode can greatly enhance BPA removal via electrooxidation. Humic acids which are abundantly present in nature can also make this removal process faster. Overall, this study highlights the great application potential of laccase‐immobilized bioelectrodes for BPA removal in conditions close to real‐life scenarios. Abstract : Laccase‐immobilized alginate/pectine is a good bioelectrode material for degradation of bisphenol A (BPA) in aqueous medium. Degradation of BPA, an ubiquious endrocrine disruptor, and of BPA intermediates, using such bioelectrode, as well as the influence of humic acids on BPA degradation efficiency are investigated. Experimental evidence shows BPA is effectively degraded into different byproducts and HAs show considerable influence on that process.